Atrial fibrillation after coronary bypass surgery: the role of ranolazine in its prevention - صالح منتجب (Latakia University Journal -Medical Sciences Series, 2023)
Introduction Atrial fibrillation is a common complication of open heart surgery, occurring in 25% to 40% of patients who undergo CABG or valve replacement. AF is associated with an increased risk of stroke following surgery and it is the most common cause of long-term hospitalization. The exact pathogenetic mechanisms causing atrial fibrillation after cardiac surgery are not precisely known. Sympathetic hyperactivation , elevated postoperative noradrenaline levels, atrial tissue ischemia, postoperative exaggerated inflammatory response, and temperature difference between the atria and ventricles during the Cardioplegia period may be involved in the pathogenesis. Many drugs have been used to prevent POAF (beta blockers, calcium blockers, amiodarone , magnesium...) but most of them have many side effects, while Ranolazine is a drug used as a dilator of coronary arteries and because of its antiarrhythmic properties through its effect on the delayed sodium and potassium channels without any significant side effects. Because of the aforementioned came the idea of this study and its importance. Methods Our study included patients admitted to the Department of Cardiac Surgery at Tishreen University Hospital during one year 2022/2023 to perform coronary artery bypass surgery (CABG) , and it included 60 patients, aged between 36-73 years ( average age: 55.87 + 8.938 ). We adopted a prospective, randomized, two-arm statistical study compared to a control group. The patients were divided into two groups (Ranolazine group, control group). Ranolazine was given at a dose of 500 mg one tablet daily 3 days before the elective surgery and continued to be given for 7 days after surgery. Placebo was also given to the control group. The occurrence of atrial fibrillation was monitored by conducting daily electrocardiograms for both groups. Results The Ranolazine group included 30 patients and two patients had Atrial fibrillation (the rate of Atrial fibrillation was 7%), while the control group included 30 patients and nine patients had Atrial fibrillation (the percentage of Atrial fibrillation was 30%). It can be seen from the foregoing that there is a decrease in the incidence of Atrial Fibrillation by 23% as a result of the administration of Ranolazine. Our study also showed a positive relationship between the occurrence of Atrial fibrillation and high blood pressure in addition of chronic obstructive pulmonary disease (COPD) , but it was not statistically significant , while there was no evidence of a relationship between the occurrence of AF and other indicators (age , gender, systolic function of the left ventricle EF , the size of the left atrium). Conclusion It was found that Ranolazine is an effective drug in the prevention of POAF, which can be used safely with few side effects , at a dose of 500 mg one tablet per day, starting 3 days before selective coronary surgery and continuing for 7 days after surgery in order to prevent the occurrence of Atrial fibrillation after coronary heart surgery. Since Ranolazine is a drug that does not have side effects like other drugs used to prevent Atrial fibrillation, we recommend that it be used more extensively in all patients undergoing heart surgery using Cardiopulmonary Bypass.